1961
DOI: 10.1099/00221287-26-3-361
|View full text |Cite
|
Sign up to set email alerts
|

The Occurrence of Polythionates as Intermediates in the Metabolism of Thiosulphate by the Thiobacilli

Abstract: SUMMARYFurther evidence for the inclusion of polythionates in the pathway of thiosulphate oxidation by members of the genus Thiobacillus is presented. Manometric experiments showed tetrathionate oxidation to be a stage in thiosulphate oxidation by suspensions of T . thioparus and T. thiocyanoxidans. Thiobltcillus thioparus accumulated a sufficient concentration of polythionate in the medium to allow chromatograms to be prepared, and the type of polythionate accumulated was influenced by the ratio between the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

1962
1962
1981
1981

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 11 publications
1
9
0
Order By: Relevance
“…Pratt (1958) showed that T. thioparus cultures accumulated polythionates at an earlier stage of growth than was the case with T. thiocyanoxidans cultures, grown aerobically in thiosulphate medium. Jones & Happold (1961), in confirming Pratt's results, showed that oxidation of the polythionates was potassium ion dependent. We have consequently attempted to define further the similarities and dissimilarities between these organisms.…”
Section: Introductionsupporting
confidence: 85%
“…Pratt (1958) showed that T. thioparus cultures accumulated polythionates at an earlier stage of growth than was the case with T. thiocyanoxidans cultures, grown aerobically in thiosulphate medium. Jones & Happold (1961), in confirming Pratt's results, showed that oxidation of the polythionates was potassium ion dependent. We have consequently attempted to define further the similarities and dissimilarities between these organisms.…”
Section: Introductionsupporting
confidence: 85%
“…Several workers have reported the accumulation of tetrathionate during the oxidation of sulphur compounds by suspensions of thiobacilli (Vishniac, 1952 ;Baalsrud & Baalsrud, 1954; Vishniac & Santer, 1957; Trudinger, 1959; Jones & Happold, 1961).…”
Section: Introductionmentioning
confidence: 99%
“…One possible explanation is that, though the same pathway may be followed, the rates of reaction differ because of inherent differences between the strains in, for example, cell-wall composition and permeability. Pratt (1958) and Jones & Happold (1961) also found that cultures of T . thiocyanoxidans produced less polythionate than cultures of T .…”
Section: Discussionmentioning
confidence: 90%